Hybrid knowledge-based expert system and multi-criteria analysis for minimizing erosion and sedimentation due to stormwater in Malaysian construction sites - Al-Ani I.A.R.; Sidek L.M.; Desa M.N.M.; Ahmad Basri N.E. (2023)
Malaysia is located in a tropical zone wherein heavy rainfall occurs in all seasons of the year. Land clearing and earthwork activities combined with heavy rainfall and the widely varied topography can result in severe soil loss that shall eventually be deposited into the adjacent water bodies via stormwater. Recently knowledge-based systems have been used in many fields especially when human expertise and data are limited. In the current study, a hybrid knowledge-based expert system and multi-criteria analysis (MCA) were developed to minimize erosion and sedimentation due to stormwater in Malaysian construction sites. This system called the Multi-criteria Erosion and Sediment Control (MCESC) system. The role of MCA is to identify the best stormwater control measure based on specified criteria and the criterion's weight. Data from road construction project in Permas Jaya, Johor Bahru State, Malaysia has been utilized for testing the MCESC system's functionality in solving real erosion and sediment control problem. The MCESC system can be used by engineers, contractors, and decision makers to develop erosion and sediment control plan and environmental management plan for any construction site in Malaysia. IWA Publishing 2012.